2009
DOI: 10.1111/j.1600-0714.2008.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, histological and immunohistochemical findings in oral Kaposi's sarcoma in a series of Mexican AIDS patients. Comparative study

Abstract: The expression of D2-40 marker in the vascular walls and SC supports the view of a lymphatic differentiation in neoplastic cells of OKS. Desmin, alpha SMA, D2-40, C-kit and HHV-8 were the main markers differently expressed in OKS and OPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
5
22
0
Order By: Relevance
“…Reliable data on D2-40 expression in classic KS cases are limited. D2-40 staining ratios ranged between 90 and 100% in neoplastic cells of KS [17,[19][20][21][22][23][24]26]. Fukunaga et al reported that D2-40 immunoreactivity was positively correlated with histological stage in KS [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliable data on D2-40 expression in classic KS cases are limited. D2-40 staining ratios ranged between 90 and 100% in neoplastic cells of KS [17,[19][20][21][22][23][24]26]. Fukunaga et al reported that D2-40 immunoreactivity was positively correlated with histological stage in KS [30].…”
Section: Discussionmentioning
confidence: 99%
“…When the disease was first defined, the tumors were thought to originate from blood vessel endothelium [10][11][12][13][14][15][16][17]. Recent trials, however, have shown that lymphatic origin or differentiation may play a key role in the histogenesis of KS [18][19][20][21][22][23][24]. Some researchers have claimed that the neoplastic cells of KS originate from endothelial progenitor cells, and that blood and lymphatic vessel endothelium may each differentiate into both cell types [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaposi's sarcoma (KS) is an angioproliferative disorder characterized by proliferation of spindle-shaped cells, neoangiogenesis, inflammation and oedema, and categorized as an intermediate neoplasm due to the absence of conventional features of malignancy [1] . It was first described in 1872 by Moritz Kaposi [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Kaposi's sarcoma is an angioproliferative disorder characterized by proliferation of spindle-shaped cells, neo-angiogenesis, inflammation and edema [29][30]. Four major forms have been identified: Classic, African endemic, Immunosuppression-associated or transplant-associated, and AIDS-associated [31][32].…”
Section: Kaposi's Sarcoma (1 Case)mentioning
confidence: 99%